Transient Severe Motion Artifact Related to Gadoxetate Disodium-Enhanced Liver MRI: Frequency and Risk Evaluation at a German Institution - Well, Lennart; Rausch, Vanessa Hanna; Adam, Gerhard; Henes, Frank Oliver; Bannas, Peter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose Varying frequencies (5 – 18 %) of contrast-related transient severe motion (TSM) imaging artifacts during gadoxetate disodium-enhanced arterial phase liver MRI have been reported. Since previous reports originated from the United States and Japan, we aimed to determine the frequency of TSM at a German institution and to correlate it with potential risk factors and previously published results.Materials and Methods Two age- and sex-matched groups were retrospectively selected (gadoxetate disodium n = 89; gadobenate dimeglumine n = 89) from dynamic contrast-enhanced MRI examinations in a single center. Respiratory motion-related artifacts in non-enhanced and dynamic phases were assessed independently by two readers blinded to contrast agents on a 4-point scale. Scores of ≥ 3 were considered as severe motion artifacts. Severe motion artifacts in arterial phases were considered as TSM if scores in all other phases were < 3. Potential risk factors for TSM were evaluated via logistic regression analysis.Results For gadoxetate disodium, the mean score for respiratory motion artifacts was significantly higher in the arterial phase (2.2 ± 0.9) compared to all other phases (1.6 ± 0.7) (p < 0.05). The frequency of TSM was significantly higher with gadoxetate disodium (n = 19; 21.1 %) than with gadobenate dimeglumine (n = 1; 1.1 %) (p < 0.001). The frequency of TSM at our institution is similar to some, but not all previously published findings. Logistic regression analysis did not show any significant correlation between TSM and risk factors (all p > 0.05).Conclusion We revealed a high frequency of TSM after injection of gadoxetate disodium at a German institution, substantiating the importance of a diagnosis-limiting phenomenon that so far has only been reported from the United States and Japan. In accordance with previous studies, we did not identify associated risk factors for TSM.Key Points: Citation Format
Keywords: contrast agents; transient severe motion artifact; MR; gadoxetate disodium; magnetic resonance imaging; transient severe artifacts; risk